Can Tests Based on Option Hedging Errors Correctly Identify Volatility Risk Premia? - Nicole Branger; Christian Schlag (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
Tests for the existence and the sign of the volatility risk premium are often based on expected option hedging errors. When the hedge is performed under the ideal conditions of continuous trading and correct model specification, the sign of the premium is the same as the sign of the mean hedging error for a large class of stochastic volatility option pricing models. We show, however, that the problems of discrete trading and model mis-specification, which are necessarily present in any empirical study, may cause the standard test to yield unreliable results.
Keywords: G12; G13; 330; Stochastic Volatility; Volatility Risk Premium; Discretization Error; Model Error; Volatilität; Risikoprämie; Statistischer Test; Optionspreistheorie; Stochastischer Prozess; Theorie